Keefektifan Model Pembelajaran Berbasis Masalah dengan Pendekatan Saintifik di Kelas XI MAN Pangkep dalam Meningkatkan Hasil Belajar - Reny, Reny; Astuti, Sry (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This pre-experimental study aims to determine the effectiveness of a problem-based learning model with a scientific approach for students in the XI IPA class at MAN Pangkep, specifically focusing on the topic of buffer solutions to improve learning outcomes. The effectiveness of the learning process is assessed through pretest and posttest results. A learning outcome test was developed with 25 items, which were validated, resulting in 20 selected items. This test was administered as a pretest during the first meeting to assess the students' initial abilities. Following this, a learning process utilizing the problem-based learning model with a scientific approach was implemented, culminating in a posttest during the final meeting. Additionally, data on student and teacher activity during the learning process were collected. The data obtained from the pretest and posttest were analyzed descriptively using the g-factor formula (N-Gain). The results indicate that the problem-based learning model with a scientific approach is effective for XI IPA students at MAN Pangkep regarding the topic of buffer solutions. This is evidenced by an average gain score of 0.47 in the moderate category, along with an average student activity rate of 61.99% and a teacher activity rate of 88.89%.